Shanghai's Bund and beyond : British banks, banknote Issuance, and monetary policy in China, 1842-1937 - Horesh, Niv (Yale series in economic and financial history., 2009)
As China emerges as a global powerhouse, this title examines its economic past and the shaping of its financial institutions.